Analysis National Integration and Disintegration of Milennial Generation in Digital Era - Eliyanti Hia, Fidelia Kirana; Lumban Tobing, Nasya Eliora; Amara Nofiandari, Ni Kadek; Mustaqim, Tasya Apriyani; Rumambo Pandin, Moses Glorino (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
Indonesia has a lot of diversity, namely ethnic, cultural, racial, and others. With so much diversity, there’s a need for national integration or an effort to unite all the different elements that exist so that a country is not divided. The purpose of writing this article is to find out the importance of integration for a nation and what are the possibilities that can arise as a threat of disintegration, especially for millennial generation in digitalization era. This research was conducted using a literature review research method with a theoretical basis obtained from collecting articles and journals published from 2019-2021. The results obtained from this research are that technological developments in this digitalization era can fade or shift the noble values ??of Pancasila and easy access the internet can lead to the spread of hoaxes that can be an opportunity to divide Indonesia. This result also have limitations because they only take theories obtained from articles that have been collected and do not conduct direct surveys to the subjects studied. The millennial generation at this time needs to know and apply Pancasila values ??in daily life so that national integration can still be maintained.